Sex differences in H7N9 influenza A virus pathogenesis. Issue 49 (8th December 2015) - Hoffmann, Julia; Otte, Anna; Thiele, Swantje; Lotter, Hannelore; Shu, Yuelong; Gabriel, Gülsah
Abstract: Sex, gender and age have an impact on incidence and severity of several infectious diseases. Here, we analyzed reported human cases of avian H7N9 influenza A virus infections for potential sex-dependent incidence and mortality. We report that females in their reproductive years display an increased tendency to die of H7N9 influenza than males (female-to-male ratio = 1.2). Next, we challenged this potential sex-dependent difference in influenza disease outcome using a mouse infection model. In general, female mice underwent more severe disease than male mice upon infection with various influenza A virus subtypes, such as H7N9, 2009 pH1N1 and H3N2. However, morbidity and mortality were most significantly affected in H7N9 influenza virus infected female mice associated with an increased inflammatory host response. Thus, our mouse infection model described here might assist future investigations on the underlying mechanisms of sex-dependent disease outcome upon zoonotic H7N9 influenza virus infection. Moreover, our findings might help to guide patient management strategies and current vaccine recommendations.